Brave NUI world. - Goth, Gregory (Communications of the ACM, 2011)
The article discusses natural user interfaces (NUIs) such as motion and depth sensing technology developed using the software development kit (SDK) for the Microsoft Kinect, an input device for the Xbox 360 video game console. John Underkoffler of Oblong Industries, Peter Ngo of the California Institute of Technology, and Amir Rubin of Sixense discuss interfaces which could replace or supplement the keyboard or mouse. Other topics include the use of NUIs in medicine, the mechanics of graphical user interfaces (GUIs), and research on the interactions between humans and robots or computers.